2016
DOI: 10.4315/0362-028x.jfp-15-246
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Chitosan Coating Incorporated with Black Pepper Essential Oil for Shelf Life Extension of Common Carp (Cyprinus carpio) during Refrigerated Storage

Abstract: Black pepper; Chitosan; Common carp; Essential oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Kosar et al () investigated antioxidant activity and phenolic compounds of sumac extracts and they found that phenolic composition include anthocyanins and hydrolysable tannins and gallic acid was the main phenolic acid in the extracts, anthocyanin fraction contained cyanidin, peonidin, pelargonidin, petunidin, and delphinidin glucosides and coumarates. Similar results were found by previous studies (Moosavi‐Nasab et al, ; Ojagh et al, ; Wenjiao et al, ; Yuan et al, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Kosar et al () investigated antioxidant activity and phenolic compounds of sumac extracts and they found that phenolic composition include anthocyanins and hydrolysable tannins and gallic acid was the main phenolic acid in the extracts, anthocyanin fraction contained cyanidin, peonidin, pelargonidin, petunidin, and delphinidin glucosides and coumarates. Similar results were found by previous studies (Moosavi‐Nasab et al, ; Ojagh et al, ; Wenjiao et al, ; Yuan et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Wenjiao et al () reported that bamboo leaves added chitosan coating treatment inhibit the growth of TVCs of silver carp. Moosavi‐Nasab et al () found that TVC value of common carp ( Cyprinus carpio ) fish treated with black pepper oil added chitosan coating was less than control samples at day 16. Yu et al () reported that chitosan coating combined with essential oil extended the microbiological shelf life of grass carp fillets to 15 days.…”
Section: Resultsmentioning
confidence: 99%
“…The development of pseudomonas and S. putrefaciens led to the formation of off‐odor during fish degradation, and was inhibited by chitosan coating enriched with essential oils, showing strong antimicrobial activities during storage (Cai, Cao, Li, Wu, et al, ). Additionally, Enterobacteria was found to grow fast in treated and control samples at the end of storage, which was in accordance with the studies for common carp (Moosavi‐Nasab et al, ) and rainbow trout fillets (Jouki et al, ). The LAB increased slowly during storage, which was attributed to the lower refrigerated temperature.…”
Section: Resultssupporting
confidence: 90%
“…Table shows the different color parameters ( L *, a *, b *, C * ab , and H 0 ab ) obtained after the application of chitosan coating with essential oils. From this table, higher L values were observed in CL, CT, and CLT samples compared with the control and CH samples at the end of storage, which is primarily attributed to the ability of chitosan as the edible coating to form strong compact insoluble polymers to keep the controlled‐release of essential oils (Moosavi‐Nasab et al, ). There were no significant correlations in a * and C * ab values among these treatments during storage.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of chitosan and thyme essential oil into ready to cook chicken product suppressed the growth of yeast and moulds more effectively than individual application of chitosan and thyme essential oil during the entire of 12 days of aerobic storage period at 4 °C (Giatrakou, Ntzimani, & Savvaidis, ). In the study of Moosavi‐Nasab et al (), both chitosan coating and chitosan coating including black pepper essential oil reduced the aerobic plate count of fish fillet during refrigerated storage.…”
Section: Resultsmentioning
confidence: 98%